Sex-Related Liver Injury Due to Alcohol Involves Activation of Kupffer Cells by Endotoxin - Ronald G Thurman (Canadian Journal of Gastroenterology)
Females have a greater susceptibility to ethanol-induced liver injury than males. Females who drink ethanol regularly and have been overweight for 10 years or more are at greater risk for both hepatitis and cirrhosis than males, and females develop ethanol-induced liver injury more rapidly and with less ethanol than males. Female rats on an enteral ethanol protocol exhibit injury more quickly than males and have widespread fatty changes over a larger portion of the liver lobule. Moreover, levels of plasma endotoxin, intracellular adhesion molecule-1, free radical adducts, infiltrating neutrophils and nuclear factor kappa B are doubled in female rat livers compared with male rat livers after enteral ethanol treatment. Additionally, estrogen treatment in vivo increases the sensitivity of hepatic macrophages or Kupffer cells to endotoxin. Evidence has been presented that Kupffer cells are pivotal in the development of ethanol-induced liver injury. Destroying Kupffer cells with gadolinium chloride or decreasing bacterial endotoxin by sterilizing the gut with antibiotics inhibits early inflammation due to ethanol. Similar results have been obtained with anti-tumour necrosis factor-alpha antibody. These data pointed to the hypothesis that ethanol-induced liver injury involves elevations in circulating endotoxin concentrations leading to activation of Kupffer cells, which causes a hypoxia-reoxygenation injury. This theory has been tested using pimonidazole, a 2-nitroimidazole marker, to quantify hypoxia in downstream, pericentral regions of the hepatic lobule. After chronic enteral ethanol treatment, pimonidazole binding doubles. Enteral ethanol also increases free radicals detected with electron spin resonance. Radical adducts, with coupling constants such as alpha-hydroxyethyl radical, have been shown to arise from ethanol. Importantly, hypoxia and radical production detected in bile are also decreased by the destruction of Kupffer cells with gadolinium chloride. These data support the hypothesis that Kupffer cells contribute to the vital sex differences in liver injury caused by ethanol.